Attractors and higher dimensions in population and molecular biology emerging research and opportunities - Zhizhin, G. V. (Gennadiĭ Vladimirovich) (Engineering Science Reference, 2019)
"This book contains a mathematical analysis of Mendel's experiments on plant hybridization. It also examines the geometric structure of nucleic acids, taking into account the higher dimension of the components"--